Exploring the nexus between climate change, political stability, and income inequality in Somalia - Abdikadir Ahmed Mohamed; Said Ahmed Osman; Ahmed Shirdoon Warsame; Abdifitah Hassan Halane; Abdirisaq Husein Dhimbil (Environmental Research Communications)
Income inequality remains a critical challenge globally, with developing nations experiencing the most severe disparities. In fragile states like Somalia, climate change and political instability exacerbate economic inequality, limiting opportunities and deepening structural inequities. This study empirically examines the impact of climate change, political stability, and macroeconomic variables—including GDP per capita, inflation, population growth, and urbanization—on income inequality in Somalia from 1980 to 2022. Using the Autoregressive Distributed Lag (ARDL) model and Fully Modified Ordinary Least Squares (FMOLS), the study explores both short-run and long-run dynamics. The findings reveal that in the long run, rising temperatures significantly increase income inequality, while GDP per capita growth reduces disparities. Political stability, though beneficial for economic growth, is associated with widening inequality, suggesting that economic gains during stable periods are not evenly distributed. Population growth exacerbates income inequality, while inflation and urbanization show no significant long-run effects. In the short run, rainfall increases inequality, while short-term temperature fluctuations temporarily reduce disparities due to seasonal labor demand. The error correction term confirms a stable long-run relationship, with approximately 36.8% of disequilibrium corrected annually. FMOLS results reinforce the robustness of these findings, emphasizing climate factors and economic growth as key determinants of inequality. These findings highlight the need for policies that mitigate climate-induced inequality, promote equitable wealth distribution, and ensure inclusive economic growth. Strengthening climate adaptation, expanding financial inclusion, stabilizing inflation, and supporting rural development are essential to fostering long-term economic equity in Somalia.